2010
DOI: 10.5194/hess-14-801-2010
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing chloride deposition in a coastal hilly area and application to chloride deposition mapping

Abstract: Abstract. Chloride is commonly used as an environmental tracer for studying water flow and solute transport in the environment. It is especially useful for estimating groundwater recharge based on the commonly used chloride mass balance (CMB) method. Strong spatial variability in chloride deposition in coastal areas is one difficulty encountered in appropriately applying the method. A high-resolution bulk chloride deposition map in the coastal region is thus needed. The aim of this study is to construct a chlo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 37 publications
5
43
0
Order By: Relevance
“…Our approach, on the other hand, depends more directly on data. In spite of these substantially different analyses, we obtained mean transit times that are relatively similar to those found by Benettin et al (2015) and Harman (2015).…”
Section: Comparison With Spectral Estimates Of Transit Time Distributsupporting
confidence: 76%
See 1 more Smart Citation
“…Our approach, on the other hand, depends more directly on data. In spite of these substantially different analyses, we obtained mean transit times that are relatively similar to those found by Benettin et al (2015) and Harman (2015).…”
Section: Comparison With Spectral Estimates Of Transit Time Distributsupporting
confidence: 76%
“…Conversely, Harman (2015) used rank StorAge Selection functions at the Lower Hafren, an approach which requires making assumptions about the parametric shape of the transit time distribution. If a gamma distribution was assumed, Harman (2015) found median transit times of 400 and 550 d for fixed and storage-dependent calculations, respectively. Our approach, on the other hand, depends more directly on data.…”
Section: Comparison With Spectral Estimates Of Transit Time Distributmentioning
confidence: 99%
“…Groundwater chloride concentration follows a geographical and topographical pattern (Guan et al, 2010): maximum concentrations of chloride are found in coastal areas, while minimum concentrations are found in inland mountainous areas (Fig. 7b).…”
Section: Chloride Mass Balance Resultsmentioning
confidence: 99%
“…Coastal distance appears to be the most significant factor controlling chloride deposition in the study area; it can reach up to 70 % of the spatial variability in chloride deposition (Guan et al, 2010). In order to compute the CMB, a comprehensive bibliographic revision was carried out looking for historic data of chloride concentration in rainfall in Galicia (Alcalá and Custodio, 2008a;Fernández-Sanjurjo et al, 1997;García-Rodeja et al, 1998;Gómez Rey et al, 2002;Prada-Sanchez et al, 1993;Silva et al, 2007;Vázquez et al, 2003).…”
Section: Chloride Mass Balance Resultsmentioning
confidence: 99%
“…Cl in groundwater originates from atmospheric deposition, of which the rate depends on a number of factors including distance to the source (oceanic or terrestrial), elevation, terrain aspect, slope, vegetation cover and climatic conditions (Hutton and Leslie, 1958;Guan et al, 2010;Bresciani et al, 2014). Groundwater Cl concentrations also depend on evapotranspiration, which leaves Cl in solution, implying its enrichment (Eriksson and Khunakasem, 1969), and on the spatial redistribution of recharge through groundwater flow.…”
Section: Using Chloridementioning
confidence: 99%